Pengaruh Pertumbuhan Ekonomi pada Sektor Industri, Pertanian, dan Perdagangan, Hotel dan Restoran terhadap Jumlah Penduduk Miskin di Wilayah Gerbangkertasusila Plus pada Tahun 2015-2019 - Diovany Anggoro; Sishadiyati Sishadiyati; Muhammad Wahed (OECONOMICUS Journal of Economics, 2021)
This study aims to analyze and examine the effect of economic growth in the industrial, agricultural and trade sectors, hotels and restaurants on the number of poor people in the Gerbangkertasusila Plus area. Based on the research results, the Industry, Agriculture, and Trade sectors have a negative and significant impact on the reduction in the number of poor people in the Gerbangkertasusila Plus area